PENDIDIKAN AGAMA ISLAM (PAI) DALAM TANTANGAN DISRUPSI SOSIOLOGIS: KONSTRUKSI KARAKTER SISWA MADRASAH TSANAWIYAH KOTA SALATIGA - Arif Khoirun Nasikhin; Nafingatun; Arya Angga Dinata Saputra; Sa’adi (STKIP Subang, 2026)
This study aims to analyze the sociological dynamics of Islamic Religious Education (PAI) in constructing student character at Madrasah Tsanawiyah (Islamic Junior High School) in Salatiga. This study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with the school principal, teachers, and students, as well as documentation at MTs Negeri Kota Salatiga. Data analysis was conducted through data reduction, data display, and conclusion drawing, using triangulation techniques to ensure the validity of the findings. Analyzing the data through the lens of Peter L. Berger and Thomas Luckmann's social construction theory, the results indicate that Islamic Religious Education functions as a mechanism for socialization and social control in addressing digital era challenges among students at MTs Negeri Kota Salatiga. Student character building is carried out through religious habituation, teacher role modeling, strengthening digital literacy, and collaboration between the school, families, and the community. The characters formed include religiosity, discipline, honesty, responsibility, social awareness, and politeness. This character-building process takes place through externalization, objectivation, and internalization. The religious values formulated by the madrasah are institutionalized into the school culture and subsequently internalized by the students as behavioral guidelines in their daily lives. This study reinforces that successful character education in the era of disruption requires synergy between the madrasah's religious culture, teacher role modeling, and the strengthening of digital literacy based on Islamic values.